Sodium-Dependent Neutral Amino Acid Transporter Type 1 Is an Auxiliary Receptor for Baboon Endogenous Retrovirus - Marin, Mariana (American Society for Microbiology, 2000)
The baboon endogenous retrovirus (BaEV) belongs to a large, widely dispersed interference group that includes the RD114 feline endogenous virus and primate type D retroviruses. Recently, we and another laboratory independently cloned a human receptor for these viruses and identified it as the human sodium-dependent neutral amino acid transporter type 2 (hASCT2). Interestingly, mouse and rat cells are efficiently infected by BaEV but only become susceptible to RD114 and type D retroviruses if the cells are pretreated with tunicamycin, an inhibitor of protein N-linked glycosylation. To investigate this host range difference, we cloned and analyzed NIH Swiss mouse ASCT2 (mASCT2). Surprisingly, mASCT2 did not mediate BaEV infection, which implied that mouse cells might have an alternative receptor for this virus. In addition, elimination of the two N-linked oligosaccharides from mASCT2 by mutagenesis, as substantiated by protein N-glycosidase F digestions and Western immunoblotting, did not enable it to function as a receptor for RD114 or type D retroviruses. Based on these results, we found that the related ASCT1 transporters of humans and mice are efficient receptors for BaEV but are relatively inactive for RD114 and type D retroviruses. Furthermore, elimination of the two N-linked oligosaccharides from extracellular loop 2 of mASCT1 by mutagenesis enabled it to function as an efficient receptor for RD114 and type D retroviruses. Thus, we infer that the tunicamycin-dependent infection of mouse cells by RD114 and type D retroviruses is caused by deglycosylation of mASCT1, which unmasks previously buried sites for viral interactions. In contrast, BaEV efficiently employs the glycosylated forms of mASCT1 that occur normally in untreated mouse cells.